Bridging the gap between marine science and policy: communicating for an informed society and decision-making - Borja, Angel; Bremner, Julie; Kopke, Kathrin; Gruber, Sigi; Alessandrini, Martin; Estrela, Alice; Kastanidi, Erasmia; Leal, Miguel C.; Uyarra, María C.; Elliott, Michael (Frontiers in Communication, 2025)
This paper emphasizes the role of effective science communication in bridging the gap between marine research and policymaking. It highlights the need for clear, objective, fit-for-purpose and engaged communication of scientific findings to policymakers and society to counter misinformation and promote informed decision-making processes. Hence, it is essential for scientists to use multiple communication channels to reach diverse audiences with clear, jargon-free language and engaging methods, tending to a holistic approach combining logical evidence-based with emotional engagement of society. Ocean literacy is key in raising public awareness and promoting behavioral changes for a new narrative on the future of the ocean. We recommend increasing funding for science communication, engaging with target audiences early, ensuring high-quality scientific evidence, and presenting positive and negative aspects of findings, showing the emotional side of the stories. Public support for marine protection and conservation policies can be enhanced, leading to effective management of marine ecosystems.